Assessing acoustic competition between sibling frog species using rhythm analysis. Issue 13 (27th May 2021) - Filer, Alannah; Burchardt, Lara S.; van Rensburg, Berndt J.
Abstract: Male frog advertisement calls are species‐specific vocalizations used to attract females for breeding. However, it is possible for environmental or biological sounds to overlap these calls in both frequency and duration resulting in signal confusion, influencing female decision and/or location abilities. It is therefore important for vocal species competing for the same acoustic space to partition their calls either spatially or temporally (via call alternation or suppression). However, frog species previously isolated from each other may not have developed appropriate adaptive behaviors, resulting in acoustic competition. This study applied rhythm analysis to track changes in calling behavior, namely changes in calling frequency (as in beats per second), of the wallum sedgefrog and the eastern sedgefrog when vocalizing alone versus in the presence of each other to assess potential acoustic competition. Our main findings demonstrated that both species significantly altered their calling behavior when exposed to each other. While we expected the increased calling activity of one species to inhibit the activity of the other to avoid signal confusion, we instead found that both species greatly increased the beat frequency of their calls when calling in the presence of each other. We also found evidence of beat frequency development in the wallum sedgefrog whereby there was always a strong initial increase in call frequency in reaction to the first vocal interruption by the eastern sedgefrog. These results support the hypothesis that the eastern sedgefrog and the wallum sedgefrog are in competition for the acoustic space in habitats where they occur together. This highlights a new threat to the vulnerable wallum sedgefrog species and may serve to inform future management practices. Using rhythm analyses to track changes in acoustic behavior can help inform on important population dynamics such as health, trajectory, and response to management, and therefore be of great benefit to the conservation of vocal species. Abstract : Male frog advertisement calls are used to attract females for breeding, and it is therefore imperative that the males are able to signal without interference from overlapping or masking calls produced by other species. We used rhythm analysis to observe and track changes in the calling behavior of two competing frog species when they were calling alone and in a shared habitat. We observed that both species increased the beat frequency of their calls in reaction to the presence of the other frog, indicating a possible response to acoustic competition. ​